Acquisitions of bankrupt and distressed firms. (2016) - Precourt, Elena; Oppenheimer, Henry
We focus on acquisitions of bankrupt firms and firms that recently emerged from Chapter 11 and compare these firms with acquired distressed firms to determine whether or not transaction timing plays a role in the outcomes of the mergers. We analyse deal premiums (or lack thereof) and evaluate post-merger operating cash flows to determine whether or not timing of the transactions impacts their effectiveness and success. We find that distressed targets sell their assets at a premium or at a discount smaller than bankrupt firms do, thereby benefiting from acquisitions more than bankrupt targets. We also find that abnormal post-merger cash flow and cumulative abnormal return changes are more pronounced for bankrupt than distressed firms, indicating that acquisitions in Chapter 11 add greater economic value for both target and its acquirer than do acquisitions outside of bankruptcy. We observe post-merger market performance improvements for bankrupt and not distressed firms.